Do gestures matter? The implications of using touchscreen devices in mathematics instruction. (December 2015) - Dubé, Adam K.; McEwen, Rhonda N.
Abstract: Touchscreen devices are increasingly used in education and are a predominant tool for everyday knowledge search. An assumption about the nature of touchscreen devices is that users intuitively understand them, which improves access to knowledge. Using a framework that includes concepts from cognitive psychology, information studies, and communication theory we explored whether users' physical interactions on a touchscreen device have consequences for their conceptual understanding of content – in this case mathematics. In the present study, adults ( n = 40) completed a number line estimation task on a tablet computer (on the line 1|——–|10, place a mark at 7) by either touching the screen in a singular location (tap) or by dragging their finger across the line to the desired location (drag). All participants then went on to use the drag gesture to complete two more tablet computer mathematics tasks assessing understanding of the continuous nature of numbers. Participants in the drag condition were more accurate on all three tasks, suggesting that the continuous nature of the gesture reinforced their continuous understanding of numbers. Gestures may influence understanding of content learned from a touchscreen. Highlights: Adult participants completed number line tasks on an iPad using either a tap or a drag gesture. Gestures that aligned with math concepts improved performance. Gestures used during touchscreen learning affect how content is understood.